The Effect of Diabetes and Education on Cognitive Function of Older People - Dey, Biplob Kumar; Rahman, Shahinoor; Rahman , Abdur; Haque, Md Rezuanul (Chittagong University Journal of Biological Sciences, 2024)
The aim of present study was to investigate the effect of diabetes on cognitive impairment of older people in relation to literacy. Total 50 older people were purposively selected from Fotepur Union of Chittagong District. Among them 30 were literate and 20 were illiterate. In each group, diabetic and non-diabetic older participants were equally incorporated. WHO five wellbeing index (WHO-5) was used to measure participant’s psychological well-being. To measure cognitive function, an adapted Bangla version of Mini Mental State Examination (BAMSE) was used. Two-way analysis of variance (ANOVA) was used to analyze data. Results revealed that diabetic older people have better cognitive function than non-diabetic older adults. Secondly, education positively affects cognitive function of older people. The Chittagong Univ. J. B. Sci.,Vol. 10(1 &2):191-199, 2020